Computational fluid dynamics (CFD) simulation of gas pressure control system - Tengku Intan Nadzrah Tengku Jamil Iklil (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Computational fluid dynamics (CFD) is a medium that modern engineers use to design and simulate engineering parts without having to buy the actual part. Gas pressure control system such as air compressors is a very common in industries. In this report, a 3D model of gas pressure control system was constructed by using ANSYS 15.0 designer modeller and the grid dependency study was performed by meshing the model into three different meshing sizes.